Respuesta :
[tex] \bf \underline{Given-} \\ [/tex]
[tex] \rm{x = \frac{ \sqrt{3} }{2} } \\ [/tex]
[tex] \bf \underline{To \: find-} \\ [/tex]
[tex]\mathsf{ \frac{1 + x}{1 + \sqrt{1 + x} } + \frac{1 - x}{1 - \sqrt{1 - x} } = ?} \\ [/tex]
[tex] \bf \underline{Solution-} \\ [/tex]
[tex] \rm{ \sqrt{1 + x} } \\ [/tex]
[tex]= \sqrt{1 + \frac{ \sqrt{3} }{2} } \:\:\:\: \: \: \: \sf{ [∵\: \:x = √3/2\:(Given)]}\\[/tex]
[tex] = \sqrt{ \frac{ 2 + \sqrt{3} }{2} } \\ [/tex]
[tex] = \sqrt{ \frac{4 + 2 \sqrt{3} }{4} } \\ [/tex]
[tex] = \sqrt{ \frac{3 + 1 + 2 \times \sqrt{3} \times 1}{4} } \\ [/tex]
[tex] = \sqrt{ \frac{( \sqrt{3} + 1 {)}^{2} }{4} } \\ [/tex]
[tex] = \frac{ \sqrt{3} + 1 }{2} \\ [/tex]
[tex]\textsf{Similarly,} \\ [/tex]
[tex]\rm{ \sqrt{1 - x} } \\ [/tex]
[tex]\rm{ = \frac{ \sqrt{3} - 1}{2} } \\ [/tex]
[tex] \rm{\therefore \: \frac{1 + x}{1 + \sqrt{1 + x} } + \frac{1 - x}{1 - \sqrt{1 - x} } } \\ [/tex]
[tex] \rm{= \frac{1 + \frac{ \sqrt{3} }{2} }{1 + \frac{ \sqrt{3} + 1 }{2} } + \frac{ 1 - \frac{ \sqrt{3} }{2} }{1 - \bigg( \frac{ \sqrt{3} - 1 }{2} \bigg) } } \\ [/tex]
[tex]\rm{= \frac{2 + \sqrt{3} }{2 + \sqrt{3} + 1 } + \frac{2 - \sqrt{3} }{2 - ( \sqrt{3} - 1)} } \\ [/tex]
[tex]\rm{= \frac{2 + \sqrt{3} }{3 + \sqrt{3} } + \frac{2 - \sqrt{3} }{3 - \sqrt{3} } } \\ [/tex]
[tex]\rm{= \frac{2 + \sqrt{3} }{3 + \sqrt{3} } \times \frac{3 - \sqrt{3} }{3 - \sqrt{3} } + \frac{2 - \sqrt{3} }{3 - \sqrt{3} } \times \frac{3 + \sqrt{3} }{3 + \sqrt{3} } } \\ [/tex]
[tex] \rm{= \frac{(2 + \sqrt{3} )(3 - \sqrt{3} ) + (2 - \sqrt{3})(3 + \sqrt{3} )}{(3 {)}^{2} - ( \sqrt{3} {)}^{2} } } \\ [/tex]
[tex]\rm{= \frac{6 - 2 \sqrt{3} + 3 \sqrt{3} - 3 + 6 + 2 \sqrt{3} - 3 \sqrt{3} - 3}{9 - 3} } \\ [/tex]
[tex]\rm{= \frac{12 - 6}{6} } \\ [/tex]
[tex]\rm{= \frac{6}{6} } \\ [/tex]
[tex]\rm{= 1} \\ [/tex]
[tex] \bf \underline{Answer-} \\ [/tex]
[tex]\mathsf{\underline{Hence, the \: value \: of \: \frac{1 + x}{1 + \sqrt{1 + x} } + \frac{1 - x}{1 - \sqrt{1 - x} } \: is \: 1}} \\ [/tex]